(untitled) (Journal of International Studies, 2025)
The armed conflict between Russia and Ukraine that began in 2022 represents a comprehensive manifestation of hybrid warfare, in which traditional military operations are combined with information warfare, cultural influence, and other multidimensional instruments. This article examines the mechanisms unfolding in the cultural and artistic spheres within the context of the conflict, including the use of symbolic letters such as “Z,” “V,” and “O” that have come to represent the war, propaganda disseminated through art, and the phenomenon of “cancel culture” directed against Russia. The study also explores the sociolinguistic meaning of newly emerged expressions in Russian and Ukrainian that have developed under the influence of the conflict. Drawing on recent research findings on the concept of hybrid warfare, the paper concludes that the cultural sphere has become an independent mechanism of political influence within hybrid warfare, deepening cultural polarization and confrontation in both countries’ domestic and external environments. Гибрид дайны “соёлын талбар”: ОХУ-Украины мөргөлдөөний жишээн дээр Хураангуй: 2022 онд эхэлсэн ОХУ-Украины зэвсэгт мөргөлдөөн нь уламжлалт цэргийн ажиллагааг мэдээллийн дайн, соёлын нөлөөлөл зэрэг олон талт хэрэгслүүдтэй хослуулсан гибрид дайны иж бүрэн илрэл болж байна. Энэхүү өгүүлэлд уг мөргөлдөөний хүрээнд соёл, урлагийн салбарт өрнөж буй механизм, түүний дотор мөргөлдөөнийг төлөөлсөн “Z”, “V”, “O” зэрэг үсгэн бэлгэдлийн хэрэглээ, урлагаар дамжсан суртал ухуулга, ОХУ-ын эсрэг өрнөсөн “татгалзах соёл”-ын үзэгдэл зэргийг шинжилсэн. Мөн орос, украин хэлэнд мөргөлдөөний нөлөөгөөр үүссэн шинэ үг хэллэгийн социолингвистик утгыг авч үзэв. Судалгаанд гибрид дайны үзэл баримтлалын талаар судлаачдын гаргасан сүүлийн үеийн үр дүнгүүдийг ашигласан бөгөөд үр дүнд нь соёлын талбар нь хосолмол буюу гибрид дайнд улс төрийн нөлөөллийн бие даасан механизм болон хувирч, хоёр улсын дотоод, гадаад орчинд соёлын туйлшрал, зөрчилдөөн гүнзгийрч буй нэгтгэн дүгнэсэн болно. Түлхүүр үгс: ОХУ, Украин, гибрид дайн, соёл, татгалзах соёл